Vau i Dejës, Albanien. Das hellenistische Heiligtum. Die Arbeiten des Jahres 2021 - Oettel, Andreas; Hoxha, Gëzim (e-Forschungsberichte des DAI, 2021)
The small Hellenistic sanctuary at Vau i Dejës (Northern Albania) was discovered in only 2015. The small village is located in the northeast of the Zadrima plain which extends between the modern cities of Shkodra and Lezha, formerly the ancient poleis of Skodra and Lissos. The site which is situated on a hill is marked by a rugged rock surface. The remarkably rich finds consist chiefly of sherds from fine Hellenistic ceramics and further of terracotta fragments from a female deity as well as Hellenistic coins and metal objects. In addition, there were some vessel fragments and coins from the period of Late Antiquity. Not one single object could be attributed to the Roman Period (1st–3rd centuries AD).